Numerical Modeling of Flexible Oscillating Water Columns for Wave Energy Conversion (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The Flexible Oscillating Water Column (FlexOWC) introduces an innovative wave energy conversion approach, using a flexible membrane to enhance energy harvesting and system efficiency. This paper presents a numerical investigation of the FlexOWC system integrated within a Coastal Structure Integrated (CSI) framework, advancing renewable energy technologies and coastal resilience. Two complementary numerical modeling techniques assessed the FlexOWC’sperformance. The computationally efficient potential flow model explored geometric and operational configurations across various wave conditions. Simultaneously, ahigh-fidelity Computational Fluid Dynamics (CFD) model developed in OpenFOAM captured hydrodynamic interactions and flexible membrane behavior, incorporatingturbulence and fluid-structure interaction models essential for understanding system dynamics. The results show substantial improvements in pneumatic power output compared to traditional rigid Oscillating Water Columns (OWCs). The flexible membrane increased power output under both regular and irregular wave conditions, attributed to its adaptive response to wave forces,creating favorable pressure distributions in the OWC chamber. These findings demonstrate the potential of flexible membrane technology to optimize energy capture in diverse wave climates. FlexOWC technology offers a scalable and sustainable solution for wave energy conversion, with dual benefits of renewable energy generation and coastal protection against extreme weather events when integrated into multifunctional coastal structures. Future work will focus on experimental validation through prototype testing and field deployment, with industry collaborations ensuring a streamlined path to commercialization and application.